Heat Treatment and Surface Treatment of Nickel–Titanium Endodontic Instruments - Kwak, Sang Won; Shen, Ya; Liu, He; Wang, Zhejun; Kim, Hyeon-Cheol; Haapasalo, Markus (Frontiers in Dental Medicine, 2021)
Knowledge and thorough understanding of the characteristics of endodontic nickel-titanium (NiTi) files is paramount for dentists performing root canal treatments to patients. Understanding the behaviour of the NiTi files guides the clinicians in choosing correct instruments for different clinical and anatomical situations. This review focuses on the metallurgical properties of endodontic NiTi files, with a special emphasis on recent developments and improvements in metallurgy, effects of heat treatment and surface treatment. The impact that such developments have on the properties of endodontic NiTi files is discussed.